﻿Effects of Zanthoxylum acanthopodium on MMP-9 and GLUT-1 expression and histology changes in rats with cervical carcinoma - Rostime Hermayerni Simanullang; Putri Cahaya Situmorang; Jekson Martiar Siahaan; Sry Suryani Widjaja; Mutiara Mutiara (Pensoft Publishers, 2022)
Cervical cancer is one of the most common cancers in Indonesia. It can be treated with molecular therapies targeting Matrix metallopeptidase 9 (MMP-9) and Glucose transporter (GLUT-1), which are enzymes that are involved in tumour cell invasion, metastasis and angiogenesis. Zanthoxylum acanthopodium (andaliman) is an Indonesian herb with anti-cancer properties. This study aimed to investigate the histological changes andaliman treatment caused in MMP-9 and GLUT-1 expression. This study used five groups of rats: control (C-), cancer model (C+), cancer-bearing rats with a 100-mg dose of Zanthoxylum acanthopodium methanol extract (ZAM)/BW (ZAM100), cancer-bearing rats with a 200-mg dose of ZAM /BW (ZAM200) and cancer-bearing rats with a 400-mg dose of ZAM/BW (ZAM400). Immunohistochemical methods were used to stain cervical tissue with MMP-9 and GLUT-1 antibodies, and a TUNEL assay was performed to investigate cell apoptosis. Zanthoxylum acanthopodium methanol extract administration did not affect rat body weight but had a significant effect on cervical cancer growth. There was an increase in MDA levels associated with SOD deficiency in tumour tissue. SOD activity increased due to ZAM administration, allowing cells to be protected from oxidant disruption and oxidative stress. ZAM ameliorated cervical carcinoma tissue damage and reduced the expression of MMP-9, GLUT-1 and apoptosis in serum and tissue (p < 0.01) In short, the higher the ZAM dose, the lower the expression of MMP-9, GLUT-1 and apoptosis, indicating that ZAM is effective to treat cervical cancer.